Pengaruh Konsentrasi Protein yang Berbeda dalam Suspensi Dedak sebagai Pakan terhadap Diameter Kista Artemia salina : Pengaruh Konsentrasi Protein yang Berbeda dalam Suspensi Dedak sebagai Pakan terhadap Diameter Kista Artemia salina - Ahmad Shofy Mubarak; Laksmi Sulmartiwi; Muhammad Daffa Al Rasyid Nurhayati (Airlangga University, 2023)
Artemia salina is a natural food that is very important in hatcheries. The need for Artemia as a natural feed for fish or shrimp seeds is high in Indonesia, so it is necessary to develop local Artemia cultivation. One way to do this is to increase the production of Artemia salina cysts by paying attention to the quality and quantity of feed, namely enrichment with ISP (Isolated Soya Protein) flour in the feed given. ISP is a protein isolated from soybeans with the final product in the form of flour, easy to digest and has high nutritional value. Enrichment with ISP flour was carried out with the aim of increasing the protein content that affects the formation of the shell and the size of the good Artemia salina cyst. This study aimed to determine the effect of different protein concentrations using ISP (Isolated Soya Protein) in bran suspension on the diameter of Artemia salina cysts. The research method used was experimental with a completely randomized design (CRD) using 5 treatments and 4 replications. The results showed that different protein concentrations by enriching ISP flour (Isolated Soya Protein) in bran suspension as feed had a significant effect (P<0.05) on Artemia salina cyst diameter in the third week. The administration of ISP with a protein concentration of 40% and 45% showed the highest Artemia salina cyst diameter.